Analisis Gadai Tanah Perspektif Hukum Ekonomi Syariah - Armawi, Armawi (PT. Riset Press International, 2025)
This research aims to discuss the practice of land pawning in Ramban Kulon village and its analysis from the perspective of Sharia Economic Law. Land pawn is a form of transaction that is allowed in Islam, but must fulfil certain conditions. This research uses normative legal research methods and legislative approaches, Ulama's hujjah and conceptual approaches. The results show that the practice of land pawning in Ramban Kulon Village is not fully in accordance with the principles of Sharia Economic Law, especially regarding the utilisation of pawned goods. Therefore, it is necessary to make adjustments and better understand the principles of Sharia Economic Law in the practice of land pawning.